Optimalisasi Perpustakaan Sekolah dalam Meningkatkan Minat Literasi Siswa Sekolah Dasar - Hikmah, Shofi Nurul; Arifin, Muh Husen (Medpro, 2024)
The purpose of this study is to evaluate the attractiveness of the school library and its impact on increasing the literacy interest of 5th-grade students at SDN Sukarasa, Cileunyi, Bandung Regency. The research uses a descriptive qualitative approach with a case study design, supported by literature studies. The library at SDN Sukarasa is not fully optimized, primarily due to space constraints preventing the establishment of a dedicated library room. However, schools and educators can take measures to encourage students' literacy development, such as creating classroom-based literacy spaces and utilizing technology for literacy activities. The findings suggest that while the library's current state hinders its effectiveness, alternative strategies can still foster student literacy. This study contributes to understanding how library conditions in elementary schools influence students' literacy interest and offers practical solutions for overcoming related challenges.